2008
DOI: 10.17221/336-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Hypodiploidy as a prominent attributor to chromosomal aneuploidy in transgenic rabbit embryos

Abstract: Transgenic animals play a vital role in basic research, agriculture and pharmaceutical industries. Rabbits have the advantage of other large laboratory species in that they have a short gestation period and yield large numbers of embryos. Production of transgenic rabbits has been directed towards using the rabbit as a model for large domestic animals or as a basic biological model for studying the mammalian gene regulation. In connection with their use, developmental and health disorders have also been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Popelková et al (2005) reported that the ability to achieve the hatching in microinjected rabbit blastocysts (94.00%) is comparable with the control group of embryos (90.00%). Microinjection of a foreign gene into the pronucleus of eggs can result in chromosomal aneuploidy (Roychoudhury et al, 2008), and DNA rearrangement during integration can cause decreased yield of blastocyst stage embryos (Voss et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Popelková et al (2005) reported that the ability to achieve the hatching in microinjected rabbit blastocysts (94.00%) is comparable with the control group of embryos (90.00%). Microinjection of a foreign gene into the pronucleus of eggs can result in chromosomal aneuploidy (Roychoudhury et al, 2008), and DNA rearrangement during integration can cause decreased yield of blastocyst stage embryos (Voss et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Over-spread metaphases were excluded, only chromosomes in metaphase plates, which were looked complete, were counted. Further, Roychoudhury et al (2008) reported 73.33% aneuploidy occurrence in cells isolated from intact control rabbit embryos in their paper, focused on the influence of transgenesis on the aneuploidy rate. Due to this, the chromosomes were dispersed on the slide within a limited space.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Roychoudhury et al . (2008) reported 73.33% aneuploidy occurrence in cells isolated from intact control rabbit embryos in their paper, focused on the influence of transgenesis on the aneuploidy rate. Viuff et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation